2007
DOI: 10.1108/02621710710777255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of satisfaction with communication on the relationship between individual‐job congruence and job performance/satisfaction

Abstract: PurposeThe purpose of this paper is to examine the moderating influence of communication satisfaction on the association between individual‐job congruence and both job performance and job satisfaction.Design/methodology/approachModerated regression analysis was used to assess data collected from 302 employees addressing the research variables of job scope, growth need strength, satisfaction with communication, job performance, and job satisfaction.FindingsSatisfaction with communication received weak support a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 55 publications
7
53
0
7
Order By: Relevance
“…Examples include Rich (1997), who shows that sales personnel are more satisfied with their jobs if they have honest bosses in whom they can place their trust; or Flaherty and Pappas (2000) who analyze the salespersonmanager relationship and conclude that trust has a major repercussion on job satisfaction. Likewise, in an empirical study in two firms Goris et al (2003) find that interpersonal trust is a determinant factor in job satisfaction. Matzler and Renzl (2006) report that trust in co-workers and in superiors are both strong drivers of job satisfaction.…”
Section: Insert Figure 1 ------------------------mentioning
confidence: 99%
“…Examples include Rich (1997), who shows that sales personnel are more satisfied with their jobs if they have honest bosses in whom they can place their trust; or Flaherty and Pappas (2000) who analyze the salespersonmanager relationship and conclude that trust has a major repercussion on job satisfaction. Likewise, in an empirical study in two firms Goris et al (2003) find that interpersonal trust is a determinant factor in job satisfaction. Matzler and Renzl (2006) report that trust in co-workers and in superiors are both strong drivers of job satisfaction.…”
Section: Insert Figure 1 ------------------------mentioning
confidence: 99%
“…Affectbased trust creates more emotional ties between individuals when individuals express their concern for personal wellbeing (e.g., the person showing attention and concern for the benefit and wellbeing of people within the team). Previous empirical research establishes that cognitive-based and affect-based trust are distinct (Ganesan & Hess, 1997) and have different effects on cross-functional working relationships (Goris et al, 2003;McAllister, 1995). Considering that cognitive-based trust refers to perceived peer reliability and professional competence, cognitive-based trust should associate positively with relationship effectiveness.…”
Section: Interpersonal Trustmentioning
confidence: 99%
“…Scholarly literature highlights the importance of interpersonal trust in intraorganizational relationships (Goris et al, 2003). Studies report an association between interpersonal trust in teams and a wide range of positive outcomes, such as increased satisfaction within the team and team commitment (Costa, 2003) and knowledge and resource exchange, which in turn enhance team performance (Walumbwa et al, 2011).…”
Section: Interpersonal Trustmentioning
confidence: 99%
“…Goris [16] suggested that open and motivating communication may produce high levels of performance and satisfaction in the organization. Integrative communication behavior facilitates the creation of trust between the parties and reduces uncertainty to reach win/win agreements and is therefore better able to satisfy the interests of the parties (Alder et al [17].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It will be intriguing to note that computer experiences such as typing skills and background knowledge are important predictors of perceptions of media richness, and lead to more satisfaction with the media. Based on the Goris [16] and Appelbaum et al [20] findings, communication without receiving feedback appears to be increasing dissatisfaction. (Table 1) shows the literature orientation among researchers of communication and media satisfaction.…”
Section: Theoretical Backgroundmentioning
confidence: 99%